Improving Community Welfare by Improving Waste Functions - Ihsan Azhari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This paper discusses the handling of household waste with 3R principles and community welfare with the factors that influence it in Pahlawan Village, Tanjung Tiram District, Batu Bara Regency. The cause of the abundance of household waste is due to the lack of public knowledge about proper waste management and can be of economic value. The absence of good waste management causes waste to accumulate so that it hurts the environment, health, and the economy of the community. This study uses the SEM (Structural Equation Modeling) method. This method is used to analyze the relationship between socio-economic factors, culture, and environmental knowledge with household waste management in Pahlawan Village, Tanjung Tiram District, Batu Bara RegencyBased on the results of the study, socio-economic factors have a significant effect on the handling of household waste and community welfare, culture has a significant effect on the handling of household waste but is not significant on the welfare of the community where the P value> 0.05, then environmental knowledge does not significantly affect the handling of household waste. where the P value> 0.05 but significantly affects the welfare of the community.